Analisis Kinerja LoRa SX1278 Menggunakan Topologi Star Berdasarkan Jarak dan Besar Data Pada WSN - Fathia Ningtyasari Aroeboesman; Mochammad Hannats Hanafi Ichsan; Rakhmadhany Primananda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Data transmission is one of the technological advancements that began to be applied in various fields such as education, military or personal needs. Data transmission is widely known as sending messages between one point to another which is useful for getting or exchanging information. Data transmission needs technology and tools that can support the process. Wireless Sensor Network is one of technology that supports transmission data based on wireless, making it easier to implement. Ones of module that can support data transmission is LoRa SX1278, support data transmission systems with a wide range of distances and capable of sending large amounts of data. In this study there are 4 LoRa modules, where 1 module function as a master module and 3 modules function as slaves. Using a star topology, data transmission is carried out between modules by passing one master module as the bridge. Where the purpose of this study is to analyze the performance of LoRa module by looking at the results of Delay, RSSI, Throughput and SNR values that are generated when data transmission takes place. In testing, the farthest distance of transmission is 300 m and the shortest distance is 10 m by sending the smallest data 1 byte and the largest is 251 bytes.